Anaerobic digestates from sewage sludge used as fertilizer on a poor alkaline sandy soil and on a peat substrate: Effects on tomato plants growth and on soil properties. (1st September 2020) - Cristina, Giulio; Camelin, Enrico; Tommasi, Tonia; Fino, Debora; Pugliese, Massimo
Abstract: Anaerobic digestates from sewage sludge (SSADs) are a by-product of the wastewater treatment process that still preserves a certain agronomic interest for its richness in plant nutrients and organic matter. Fertilizing properties of two liquid and two dewatered SSADs were tested on tomato plants ( Solanum lycopersicum L.). Pot experiments were performed on sandy soil and peat substrate under greenhouse conditions with a SSADs application rate of 170 kg N/ha over a period of three months. Beneficial effects of SSADs were reported on different growth parameters, revealing an increase in biomass and height up to 37.5 and 6-folds over untreated control. No phytotoxic effect occurred on SSAD-exposed plants. Chemical analysis of soils treated with SSADs showed enrichment of macro- and micro-nutrients as well as organic matter. In some cases, the chemical characterization of leaves revealed an enhancement of uptaken macronutrients. This study contributed in general to deepen the knowledge on the short-term growing season fertilizing effects of SSAD. Despite the treatment dosage was calculated only on nitrogen requirements, the study highlighted the importance of the other nutrients and organic matter on plant growth. Graphical abstract: Image 1 Highlights: Anaerobic digestates from sewage sludge increased plant biomass up to 37.5-folds. No phytotoxic effect occurred on plants exposed to anaerobic digestates. Digestates application induced soil enrichment in nutrients and organic matter.